PERAN DAN KEDUDUKAN PESERTA DIDIK DALAM PENYELENGGARAAN MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) DI SMA (Studi Exploratif Mengenai Eksistensi PJOK Dari Perspektif Peserta Didik) (Journal of Physical Education and Sports, 2015)
Tujuan penelitian untuk mengetahui persepsi peserta didik terhadap penyelenggaraan mata  pelajaran PJOK, pemahaman peserta didik terhadap mata pelajaran PJOK, menggali peran dan kedudukan peserta didik terhadap konstruksi perencanaan pembelajaran mata pelajaran PJOK. Penelitian ini adalah deskriptif kuantitatif. Populasi penelitian delapan SMA Negeri kota semarang peringkat 8 sampai 16 berdasarkan hasil UN tahun 2013-2014. Sampel dalam penelitian ini berjumlah 754 responden Hasil penelitian diperoleh persepsi peserta didik terhadap penyelenggaraan mata pelajaran PJOK adalah baik, Pemahaman peserta didik terhadap PJOK adalah baik. Peran dan kedudukan peserta didik terhadap konstruksi perencanaan pembelajaran PJOK cukup baik. Kesimpulan penelitian ini yaitu peserta didik pada jenjang pendidikan SMA adalah penerima aksi pendidikan memiliki peran dan kedudukan terhadap penyelenggaraan mata pelajaran PJOK. Disarankan bagi sekolah dan guru PJOK harus memperhatikan/melibatkan peserta didik dalam prsoses dan konstruksi pelaksanaan pembelajaran sebagai kajian untuk meningkatkan kualitas hasil pembelajaran PJOK. This study aimed to determine the perceptions of learners towards implementation of PJOK subject, to know the students’ understanding of the PJOK subject, to explore the role and position of learners towards planning the construction of studying PJOK subject. The results obtained perceptions of the students for the implementation PJOK is good. The understanding the students against PJOK is good. The role and status of the students against learning plan PJOK construction good enough. The conclusion was the students in high school education were the recipient of education action also had the role and status for the implementation PJOK. Recommended for schools and teachers PJOK subject to be able to give attention and to involve the students in the learning process and implementation studies construction to improve the quality PJOK subject learning outcomes.This study aimed to determine the perceptions of learners towards implementation of PJOK subject, to know the students’ understanding of the PJOK subject, to explore the role and position of learners towards planning the construction of studying PJOK subject. The results obtained perceptions of the students for the implementation PJOK is good. The understanding the students against PJOK is good. The role and status of the students against learning plan PJOK construction good enough. The conclusion was the students in high school education were the recipient of education action also had the role and status for the implementation PJOK. Recommended for schools and teachers PJOK subject to be able to give attention and to involve the students in the learning process and implementation studies construction to improve the quality PJOK subject learning outcomes.